3(x+7)-4(x+3)=10

Simple and best practice solution for 3(x+7)-4(x+3)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+7)-4(x+3)=10 equation:


Simplifying
3(x + 7) + -4(x + 3) = 10

Reorder the terms:
3(7 + x) + -4(x + 3) = 10
(7 * 3 + x * 3) + -4(x + 3) = 10
(21 + 3x) + -4(x + 3) = 10

Reorder the terms:
21 + 3x + -4(3 + x) = 10
21 + 3x + (3 * -4 + x * -4) = 10
21 + 3x + (-12 + -4x) = 10

Reorder the terms:
21 + -12 + 3x + -4x = 10

Combine like terms: 21 + -12 = 9
9 + 3x + -4x = 10

Combine like terms: 3x + -4x = -1x
9 + -1x = 10

Solving
9 + -1x = 10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -1x = 10 + -9

Combine like terms: 9 + -9 = 0
0 + -1x = 10 + -9
-1x = 10 + -9

Combine like terms: 10 + -9 = 1
-1x = 1

Divide each side by '-1'.
x = -1

Simplifying
x = -1

See similar equations:

| 12+50=949.88 | | 6y+(-4)= | | -2x=5x-9x+16-10 | | 7=.75*20+4 | | -3/4*8 | | 3+66x=33x+22 | | -x/4=-22 | | 4(7x+1)=312 | | .6h=1.8 | | 2(3y-6)= | | 8x+3y=101 | | -4(8+5x)=-32 | | 14=4a+2 | | 5x+11=7-2x | | -94=-2(5m+7) | | -2(7x-5)+3=-14x+13 | | p/7=6.8.k/4=2 | | 3x+11=12+8x | | 193=-x+96 | | -9x-13=50 | | 60x-3x^/3x | | 7(2x+2)=-84 | | 6x-8=6(x-5) | | 23=8*1+y | | 6460-h=4181 | | 1/4=b=3.4 | | 4.6d=26.68 | | 16x-6x=56 | | 10x+7=3x+15 | | 2/3(6x-12)=-16 | | 2/3(6x-12)=- | | 440=(11)(x)(x-3) |

Equations solver categories